Insulin Secretory Defects and Determinants of Attending at a Tertiary Hospital in Northern Region of Bangladesh (Anwer Khan Modern Medical College Journal, 2019)
Background: Bangladesh has one of the largest diabetic populations in the world and its Rajshahi region has distinct geographical and cultural identity. Determinants and basic defects of the disorder which vary substantially among populations due to racial and environmental heterogeneity.Materials & Methods: This study was conducted to characterize the new patients attending the Rajshahi  Diabetic Center which gives an idea about the proportion and risk indicators of DM among people in the  Rajshahi region. It was a hospital based observational analytic study with a hybrid research strategy having  both cross-sectional and nested case-control designs. A multistage sampling technique was followed with  660 subjects.Results: Out of the total subjects attending the OPD of RDC for the first time, 65% were found to suffer  from T2 DM. mostly (75%) of middle age (37% within 30-40 yrs and 37% within 41-50 yrs), only 2%  cases had age 51yrs. The mean ±SD calorie consumption (2549±637) of the  diabetic subjects was higher than that in non-T2 DM subjects and it came mainly from CHO (59.3%) and  fat (55.9%). 47.3% of subjects were normal weight, 36.1% over weight and 16.6% obese. Fasting serum  Insulin was significantly higher in the T2 DM group as compared to non-T2DM (Serum Insulin level  µIU/ml, M±SD) (13.5±4.9) subjects (p=